A concept of dual-responsive prodrugs based on oligomerization-controlled reactivity of ester groups: an improvement of cancer cells versus neutrophils selectivity of camptothecin - Klemt, Insa; Reshetnikov, Viktor; Dutta, Subrata; Bila, Galyna; Bilyy, Rostyslav; Cuartero, Itziar Cossío; Hidalgo, Andrés; Wünsche, Adrian; Böhm, Maximilian; Wondrak, Marit; Kunz-Schughart, Leoni A.; Tietze, Rainer; et al. (RSC Medicinal Chemistry, 2024)
Many known chemotherapeutic anticancer agents exhibit neutropenia as a dose-limiting side effect. In this paper we suggest a prodrug concept solving this problem for camptothecin (HO-cpt). The prodrug is programmed according to Boolean “AND” logic. In the absence of H2O2 (trigger T1), e.g. in the majority of normal cells, it exists as an inactive oligomer. In cancer cells and in primed neutrophils (high H2O2), the oligomer is disrupted forming intermediate (inactive) lipophilic cationic species. These are accumulated in mitochondria (Mit) of cancer cells, where they are activated by hydrolysis at mitochondrial pH 8 (trigger T2) with formation of camptothecin. In contrast, the intermediates remain stable in neutrophils lacking Mit and therefore a source of T2. In this paper we demonstrated a proof-of-concept. Our prodrug exhibits antitumor activity both in vitro and in vivo, but is not toxic to normal cell and neutrophils in contrast to known single trigger prodrugs and the parent drug HO-cpt.
CRIS-Team Scopus Importer:2024-04-19

Chemical Tools for Targeted Amplification of Reactive Oxygen Species in Neutrophils - Reshetnikov, Viktor; Hahn, Jonas; Maueroeder, Christian; Czegley, Christine; Munoz, Luis Enrique; Herrmann, Martin; Hoffmann, Markus; Mokhir, Andriy (Frontiers in Immunology, 2018)
A number of chemical compounds are known, which amplify the availability of reactive oxygen species (ROS) in neutrophils both in vitro and in vivo. They can be roughly classified into NADPH oxidase 2 (NOX2)-dependent and NOX2-independent reagents. NOX2 activation is triggered by protein kinase C agonists (e.g., phorbol esters, transition metal ions), redox mediators (e.g., paraquat) or formyl peptide receptor (FPR) agonists (e.g., aromatic hydrazine derivatives). NOX2-independent mechanisms are realized by reagents affecting glutathione homeostasis (e.g., L-buthionine sulfoximine), modulators of the mitochondrial respiratory chain (e.g., ionophores, inositol mimics, and agonists of peroxisome proliferator-activated receptor gamma) and chemical ROS amplifiers [e.g., aminoferrocene-based prodrugs (ABPs)]. Since a number of inflammatory and autoimmune diseases, as well as cancer and bacterial infections, are triggered or enhanced by aberrant ROS production in neutrophils, it is tempting to use ROS amplifiers as drugs for the treatment of these diseases. However, since the known reagents are not cell specific, their application for treatment likely causes systemic enhancement of oxidative stress, leading to severe side effects. Cell-targeted ROS enhancement can be achieved either by using conjugates of ROS amplifiers with ligands binding to receptors expressed on neutrophils (e.g., the GPI-anchored myeloid differentiation marker Ly6G or FPR) or by designing reagents activated by neutrophil function [e.g., phagocytic activity or enzymatic activity of neutrophil elastase (NE)]. Since binding of an artificial ligand to a receptor may trigger or inhibit priming of neutrophils the latter approach has a smaller potential for severe side effects and is probably better suitable for therapy. Here, we review current approaches for the use of ROS amplifiers and discuss their applicability for treatment. As an example, we suggest a possible design of neutrophil-specific ROS amplifiers, which are based on NE-activated ABPs.
EVALuna2:213257

Cyanine- and Rhodamine-Derived Alkynes for the Selective Targeting of Cancerous Mitochondria through Radical Thiol-Yne Coupling in Live Cells - Köckenberger, Johannes; Klemt, Insa; Sauer, Caroline; Arkhypov, Anton; Reshetnikov, Viktor; Mokhir, Andriy; Heinrich, Markus (Chemistry - A European Journal, 2023)
Despite their long history and their synthetic potential underlined by various recent advances, radical thiol-yne coupling reactions have so far only rarely been exploited for the functionalization of biomolecules, and no examples yet exist for their application in live cells - although natural thiols show widespread occurrence therein. By taking advantage of the particular cellular conditions of mitochondria in cancer cells, we have demonstrated that radical thiol-yne coupling represents a powerful reaction principle for the selective targeting of these organelles. Within our studies, fluorescently labeled reactive alkyne probes were investigated, for which the fluorescent moiety was chosen to enable both mitochondria accumulation as well as highly sensitive detection. After preliminary studies under cell-free conditions, the most promising alkyne-dye conjugates were evaluated in various cellular experiments comprising analysis by flow cytometry and microscopy. All in all, these results pave the way for improved future therapeutic strategies relying on live-cell compatibility and selectivity among cellular compartments.
CRIS-Team Scopus Importer:2023-06-30
Keywords: alkynes; mitochondria; radicals; selective targeting; thiols

Evaluation of N-alkylaminoferrocenes for in-vivo imaging of reactive oxygen species activity using PET and optical imaging - Toms, Johannes; Maschauer, Simone; Daum, Steffen; Reshetnikov, Viktor; Mokhir, Andriy; Prante, Olaf (JOURNAL OF LABELLED COMPOUNDS & RADIOPHARMACEUTICALS, 2019)
CRIS-Team WoS Importer:2019-06-18

Intracellular amplifiers of reactive oxygen species affecting mitochondria as radiosensitizers - Xu, Honggui; Reshetnikov, Viktor; Wondrak, Marit; Eckhardt, Lisa; Kunz-Schughart, Leoni A.; Janko, Christina; Tietze, Rainer; Alexiou, Christoph; Borchardt, Hannes; Aigner, Achim; Gong, Wenjie; Schmitt, Michael; et al. (Cancers, 2022)
Radiotherapy (RT) efficacy can be improved by using radiosensitizers, i.e., drugs enhancing the effect of ionizing radiation (IR). One of the side effects of RT includes damage of normal tissue in close proximity to the treated tumor. This problem can be solved by applying cancer specific radiosensitizers. N-Alkylaminoferrocene-based (NAAF) prodrugs produce reactive oxygen species (ROS) in cancer cells, but not in normal cells. Therefore, they can potentially act as cancer specific radiosensitizers. However, early NAAF prodrugs did not exhibit this property. Since functional mitochondria are important for RT resistance, we assumed that NAAF prodrugs affecting mitochondria in parallel with increasing intracellular ROS can potentially exhibit synergy with RT. We applied sequential Cu+-catalyzed alkyne-azide cycloadditions (CuAAC) to obtain a series of NAAF derivatives with the goal of improving anticancer efficacies over already existing com-pounds. One of the obtained prodrugs (2c) exhibited high anticancer activity with IC50 values in the range of 5–7.1 µM in human ovarian carcinoma, Burkitt’s lymphoma, pancreatic carcinoma and T-cell leukemia cells retained moderate water solubility and showed cancer specificity. 2c strongly affects mitochondria of cancer cells, leading to the amplification of mitochondrial and total ROS production and thus causing cell death via necrosis and apoptosis. We observed that 2c acts as a radiosensitizer in human head and neck squamous carcinoma cells. This is the first demonstration of a synergy between the radiotherapy and NAAF-based ROS amplifiers.
CRIS-Team Scopus Importer:2022-01-07
Keywords: Cancer; Mitochondrion; N-alkylaminoferrocene; Prodrug; Radiotherapy; Reactive oxygen species

Lysosome-targeting amplifiers of reactive oxygen species as anticancer prodrugs - Daum, Steffen; Reshetnikov, Viktor; Sisa, Miroslav; Dumych, Tetyana; Lootsik, Maxim D.; Bilyy, Rostyslav; Bila, Evgenia; Janko, Christina; Alexiou, Christoph; Herrmann, Martin; Sellner, Leopold; Mokhir, Andriy (Angewandte Chemie-International Edition, 2017)
Cancer cells produce elevated amounts of reactive oxygen species that has been used to design cancer specific prodrugs. Their activation relies on at least a bimolecular process, where a prodrug reacts with ROS. However, at low µM concentrations of the prodrugs and ROS the activation is usually inefficient. Herein we suggested and validated a potentially general approach for solving this intrinsic problem of ROS-dependent prodrugs. In particular, known 4-(N-ferrocenyl-N-benzylaminocarbonyloxymethyl)phenylboronic acid pinacol ester was converted to its lysosome specific analogue. Since lysosomes contain the higher concentration of active ROS than cytoplasm, activation of the latter prodrug was facilitated with respect to the parent compound. In particular, it was found to exhibit high anticancer activity in a variety of cancer cell lines (IC50 3.5-7.2 µM) and in vivo (40 mg/kg, NK/Ly murine model), but remained weakly toxic towards non-malignant cells (IC50 15-30 µM).
EVALuna2:13450

N-Alkylaminoferrocene-Based Prodrugs Targeting Mitochondria of Cancer Cells - Reshetnikov, Viktor; Özkan, Hülya; Daum, Steffen; Janko, Christina; Alexiou, Christoph; Sauer, Caroline; Heinrich, Markus; Mokhir, Andriy (Molecules, 2020)
Intracellular concentration of reactive oxygen species (e.g., H2O2) in cancer cells is elevated over 10-fold as compared to normal cells. This feature has been used by us and several other research groups to design cancer specific prodrugs, for example, N-alkylaminoferrocene (NAAF)-based prodrugs. Further improvement of the efficacy of these prodrugs can be achieved by their targeting to intracellular organelles containing elevated reactive oxygen species (ROS) amounts. For example, we have previously demonstrated that lysosome-targeted NAAF-prodrugs exhibit higher anticancer activity in cell cultures, in primary cells and in vivo (Angew. Chem. Int. Ed. 2017, 56, 15545). Mitochondrion is an organelle, where electrons can leak from the respiratory chain. These electrons can combine with O2, generating O2-• that is followed by dismutation with the formation of H2O2. Thus, ROS can be generated in excess in mitochondria and targeting of ROS-sensitive prodrugs to these organelles could be a sensible possibility for enhancing their efficacy. We have previously reported on NAAF-prodrugs, which after their activation in cells, are accumulated in mitochondria (Angew. Chem. Int. Ed. 2018, 57, 11943). Now we prepared two hybrid NAAF-prodrugs directly accumulated in mitochondria and activated in these organelles. We studied their anticancer activity and mode of action. Based on these data, we concluded that ROS produced by mitochondria is not available in sufficient quantities for activation of the ROS-responsive prodrugs. The reason for this can be efficient scavenging of ROS by antioxidants. Our data are important for the understanding of the mechanism of action of ROS-activatable prodrugs and will facilitate their further development.
CRIS-Team Scopus Importer:2020-06-16
Keywords: cancer; mitochondrion; N-alkylaminoferrocene; prodrug; reactive oxygen species

Radiosynthesis of an 18 F-fluoroglycosylated aminoferrocene for in-vivo imaging of reactive oxygen species activity by PET - Toms, Johannes; Reshetnikov, Viktor; Maschauer, Simone; Mokhir, Andriy; Prante, Olaf (Journal of Labelled Compounds & Radiopharmaceuticals, 2018)
The imaging of reactive oxygen species (ROS) at the molecular level with high sensitivity and specificity by positron emission tomography (PET) could be of enormous interest to increase our knowledge about ROS activity and signalling, especially in tumours. The aim of this research was to optimise the click chemistry-based radiosynthesis of an 18 F-labelled aminoferrocene glycoconjugate that was derived from an N-alkylaminoferrocene lead structure known to have anticancer activity in vitro. Applying the solvent system phosphate buffer/THF (12/5), Cu(OAc)2 and sodium ascorbate as reducing agent at 60°C, the alkyne 1 reacted with the 18 F-labelled glycosyl azide [18 F]2 in the presence of carrier 3 (47μM) to obtain carrier-added [18 F]4 in a radiochemical yield of 85%. Interestingly, the addition of carrier was essential for sufficient radiochemical yield, because it suppressed the oxidation of no-carrier-added (n.c.a.) [18 F]4. Future work will include the formulation of c.a. [18 F]4 for studying its biodistribution in tumour-bearing mice.
EVALuna2:212380

ROS-Responsive N-Alkylaminoferrocenes for Cancer-Cell-Specific Targeting of Mitochondria - Reshetnikov, Viktor; Daum, Steffen; Janko, Christina; Karawacka, Weronika; Tietze, Rainer; Alexiou, Christoph; Paryzhak, Solomiya; Dumych, Tetiana; Bilyy, Rostyslav; Tripal, Philipp; Schmid, Benjamin; Palmisano, Ralf; et al. (Angewandte Chemie International Edition, 2018)
Mitochondrial membrane potential is more negative in cancer cells than in normal cells, allowing cancer targeting by delocalized lipophilic cations (DLCs). However, as the difference is rather small, these drugs affect also normal cells. Now a concept of pro-DLCs is proposed based on an N-alkylaminoferrocene structure. These prodrugs are activated by the reaction with reactive oxygen species (ROS) forming ferrocenium-based DLCs. Since ROS are overproduced in cancer, the high-efficiency cancer-cell-specific targeting of mitochondria could be achieved as demonstrated by fluorescence microscopy in combination with two fluorogenic pro-DLCs in vitro and in vivo. We prepared a conjugate of another pro-DLC with a clinically approved drug carboplatin and confirmed that its accumulation in mitochondria was higher than that of the free drug. This was reflected in the substantially higher anticancer effect of the conjugate.
EVALuna2:35451